The First Letter to the Corinthians - Ciampa, Roy E. 1958-; Rosner, Brian S. 1959- (Chicago Wm. B. Eerdmans Publishing Co., 2010)
Intro -- Title Page -- Copyright -- Contents -- Editor's Preface -- Authors' Preface -- Chief Abbreviations -- Select Bibliography -- Introduction -- I. The Church in Corinth -- A. Roman Corinth -- B. The Church "Belonging to God" -- II. The Identity and Aims of the Apostle Paul -- A. Paul the Jew -- B. Paul the Roman Citizen -- C. Paul the Follower of Jesus -- D. Paul the Eschatological Herald -- E. Paul the Apostle to the Gentiles -- 1. The Dynamics of Pagan Sin-Romans 1 -- 2. Gentile Conversion-1 Thessalonians 1:9-10 -- 3. Paul's Missionary Agenda-Romans 15 -- III. The Interpretation of 1 Corinthians -- A. The Structure of 1 Corinthians -- B. The Argument of 1 Corinthians -- C. The Biblical-Theological Framework of 1 Corinthians -- 1. Two Key Old Testament Texts -- 2. Four Key Themes -- D. 1 Corinthians in Recent Research -- 1. Biblical and Jewish Background -- 2. Greco-Roman Foreground -- 3. The Social Sciences -- 4. Classical Rhetoric -- 5. Theology and Exposition -- E. Some Features of This Commentary -- 1. The Use of Greek and the Question of Verbal Aspect -- 2. The Format of Major Sections -- 3. The Value of 1 Corinthians -- 4. A Biblical/Jewish Approach to the Letter -- Commentary on 1 Corinthians -- I. Letter Opening, 1:1-9 -- A. Salutation, 1:1-3 -- 1. The Sender(s): Paul, Apostle of Jesus Christ (and Sosthenes), 1:1 -- 2. The Addressees: The Church in Corinth as God's Holy People under the Universal Lordship of Christ, 1:2 -- 3. The Greeting: Divine Eschatological Blessing, 1:3 -- B. Thanksgiving, 1:4-9 -- 1. For the Grace of God Already Received in Christ, 1:4-6 -- 2. For the Gifts of Grace Which Sustain Us Until Our Anticipated Approval by God on the Day of the Lord Jesus, 1:7-9 -- II. True and False Wisdom and Corinthian Factionalism, 1:10-4:17 -- A. Request for Unity, 1:10-17 -- 1. Initial Request, 1:10.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books